"Open Sesame" to the complexity of pattern recognition receptors of myeloid-derived suppressor cells in cancer - Wang, Tian; Hu, Yushu; Dusi, Silvia; Qi, Fang; Sartoris, Silvia; Ugel, Stefano; De Sanctis, Francesco (Frontiers in Immunology, 2023)
Pattern recognition receptors are primitive sensors that arouse a preconfigured immune response to broad stimuli, including nonself pathogen-associated and autologous damage-associated molecular pattern molecules. These receptors are mainly expressed by innate myeloid cells, including granulocytes, monocytes, macrophages, and dendritic cells. Recent investigations have revealed new insights into these receptors as key players not only in triggering inflammation processes against pathogen invasion but also in mediating immune suppression in specific pathological states, including cancer. Myeloid-derived suppressor cells are preferentially expanded in many pathological conditions. This heterogeneous cell population includes immunosuppressive myeloid cells that are thought to be associated with poor prognosis and impaired response to immune therapies in various cancers. Identification of pattern recognition receptors and their ligands increases the understanding of immune-activating and immune-suppressive myeloid cell functions and sheds light on myeloid-derived suppressor cell differences from cognate granulocytes and monocytes in healthy conditions. This review summarizes the different expression, ligand recognition, signaling pathways, and cancer relations and identifies Toll-like receptors as potential new targets on myeloid-derived suppressor cells in cancer, which might help us to decipher the instruction codes for reverting suppressive myeloid cells toward an antitumor phenotype.